Making home work : domesticity and Native American assimilation in the American West, 1860-1919 - Simonsen, Jane E. (Gender & American culture., 2006)
During the westward expansion of America, white middle-class ideals of home and domestic work were used to measure differences between white and Native American women. Treating white and indigenous women's struggles as part of the same history, Simonsen argues that as both cultural workers and domestic laborers insisted upon the value of their work to "civilization," they exposed the inequalities integral to both the nation and the household. Includes analysis of texts and images created by writers, women's rights activists, reformers, anthropologists, photographers, field matrons, a